Kinerja Keuangan dan Kinerja Non Keuangan terhadap Daya Saing Daerah Kabupaten Bungo - Musthafa Luthfi; Albetris Albetris; Rahayu Rahayu; Sumantri Sumantri (Universitas Batanghari, 2023)
This study aims first, to determine the effect of financial performance and non-financial performance on regional competitiveness in Bungo Regency. Second, to determine the effect of capital expenditure on regional competitiveness in Bungo Regency. Third, to determine the effect of budget management on regional competitiveness in Bungo Regency. Fourth, to determine the effect of financial performance and non-financial performance on regional competitiveness through capital expenditure in Bungo Regency. Fifth, to determine the effect of financial performance and non-financial performance on regional competitiveness through budget management in Bungo Regency. The data used in this study is primary data collected by direct interviews with respondents with predetermined criteria. This research uses Structural Equation Model (SEM) Analysis and uses Smart PLS tool. The results of the study are that first, financial performance and non-financial performance have a significant effect on regional competitiveness in Muaro Bungo Regency. Second, capital expenditure has no significant effect on regional competitiveness in Muaro Bungo Regency. Third, budget management has a significant effect on regional competitiveness in Muaro Bungo Regency. Fourth, financial performance and non-financial performance have no significant effect on regional competitiveness through capital expenditure in Muaro Bungo Regency. Fifth, financial performance and non-financial performance have a significant effect on regional competitiveness through budget management in Muaro Bungo Regency.